QUANTITATIVE ANALYSIS OF DETERMINANTS OF POVERTY IN PAYAKUMBUH CITY - Weriantoni; Hafiza Hafiza; Dasatry Dwi Ramadona; Mesi Andri Diana; Nur Ari Sufiawan; Fatma Poni Mardiah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Poverty is a complex issue that consistently draws attention from governments at both the national and regional levels. This study aims to identify and analyze the factors that influence the poverty level in Payakumbuh City using a quantitative approach through logistic regression analysis. The variables used include economic growth, the Human Development Index (HDI), government expenditure, and cigarette consumption. The results of the analysis indicate that several variables have a significant relationship with poverty levels. This study is expected to provide valuable input for local governments in formulating more effective poverty alleviation policies.